Michael Jackson's malt whisky companion : a connoisseur's guide to the malt whiskies of Scotland - Jackson, Michael, 1942- (Dorling Kindersley, 1989)
This survey of the full range of single-malt Scotch whiskies covers over 200 different varieties in detail, explaining the alterations that age, strength and geographical location make on the taste. The author has also included a section on malts made in Ireland, Asia and Japan.